2017
DOI: 10.3382/ps/pew256
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle size of the main cereal of the diet on egg production, gastrointestinal tract traits, and body measurements of brown laying hens

Abstract: The influence of the screen size used to grind the main cereal of the diet on egg production, gastrointestinal tract (GIT) development, and body measurements was studied in hens from 17 to 49 wk of age. Diets formed a 2 × 5 factorial with 2 main cereals (corn vs. barley) and 5 screen sizes of the cereal (4, 6, 8, 10, and 12 mm). Each treatment was replicated 5 times. No interactions between main cereal and screen size were observed for any of the traits studied. Cereal type and screen size did not affect feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
6
19
1
1
Order By: Relevance
“…On the other hand, the GMD and the GSD of the diets increased as the screen size used to grind the cereals increased. Similar results comparing these three cereals were reported by Perez-Bonilla et al (2014) and Herrera et al (2017), indicating that the structure of the feed depends not only on the size of the screen used but also on the characteristics of the grain.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…On the other hand, the GMD and the GSD of the diets increased as the screen size used to grind the cereals increased. Similar results comparing these three cereals were reported by Perez-Bonilla et al (2014) and Herrera et al (2017), indicating that the structure of the feed depends not only on the size of the screen used but also on the characteristics of the grain.…”
Section: Discussionsupporting
confidence: 78%
“…The information available on the effects of main cereal of the diet on egg size is scarce. Herrera et al (2017) observed that egg size was greater in hens fed barley that in hens fed corn, in agreement with the data reported herein. In contrast, Coon et al (1988) and Pérez-Bonilla et al (2011) reported similar egg size in hens fed barley based diets than in hens fed corn based diets.…”
Section: Main Cereal Of the Dietsupporting
confidence: 83%
See 3 more Smart Citations